Site-specific deterministic and probabilistic tsunami hazard assessment for Diba-Oman and Diba-Al-Emirates - El-Hussain, Issa (2021)
Destructive tsunamis were reported in the Oman Sea after large earthquakes. The Northern Sultanate of Oman and United Arab Emirates (UAE) were subjected to two confirmed tsunamis on 27 November 1945, caused by an Mw 8.1 earthquake in Makran subduction zone, and on 24 September 2013 following the Mw 7.7 Baluchistan earthquake. In this study, deterministic and probabilistic tsunami hazard assessments are performed for the coasts of Diba-Oman and Diba-UAE, which are located on the western coast of the Oman Sea. The tsunami risk of these coasts increases due to the construction of many infrastructures and urban concentration in these localities. The study focuses on earthquake-induced tsunamis, thus requiring the estimation of the maximum credible earthquake. The generation area is the Makran subduction zone, which is divided herein into EMSZ (East Makran subduction zone) and WMSZ (West Makran subduction zone). The maximum credible earthquakes of Mw 8.8 for the EMSZ and Mw 7.2 for the WMSZ are utilized as specific scenarios for the deterministic approach. The Mw 8.8 EMSZ scenario results in a maximum tsunami inundation distance of more than 300 m. Maximum inundation distance larger than 300 m occurs due to the Mw 7.2 western MSZ scenario. For these scenarios, numerical simulations show a maximum flow depth exceeding 1.75 m. The probabilistic hazard assessment utilizes the logic tree approach to estimate the probability of exceedance of 0.25, 0.5, 0.75, and 1.0 m wave height in 100 and 500 years exposure times. This analysis indicates that the likelihood that a maximum wave height exceeds 0.5 m ranges from 10 to 40% in 100 years and from 30 to 80% in 500 years.